A Review of Reversible Data Hiding-Encrypted Image (RDH-EI) Methods - Hammod, Dalal Naeem (Journal of engineering sciences and information technology, 2022)
In the past few years, the world had witnessed a revolution in multimedia and Information Technology (IT) development and utilization. This results from the increase of the internet-based-communications including the transfer of the digital data in text files, audio, video, and/or image formats. Which is why, multimedia and IT became one of the crucial parts of people’s daily lives. There are numerous threats that target Image integrity, confidentiality, and authentication, therefore, the information security is a very important concept. The Reversible Data Hiding (RDH) is a data hiding method. RDH-Encrypted Image (RDH-EI) procedure which is working through embedding additional data to an image had emerged. Lately, the RDH-EI with the wide range is used, which is why, it has attracted the interest and focus of the employers as well as the academics. Thus, a survey that discusses previous researches will be carried out for the purpose of identifying the most significant (RDH-EI) approaches throughout the past five years. Several methods of RDH-EI with the different embedding rate, when its value is low (< 0.1 bpp), it is impossible to reconstruct the image without fault. Otherwise in the case where the embedding rate is high (>0.1 bpp), it is possible to obtain an image that is quite similar to the original image but it still needed for preprocessing step.
Keywords: Reversible Data Hiding; RDH-EI; Embedding Algorithm; Extraction Algorithm